Analysis of Waste in Electronic ID Card Services with Lean Service and Root Cause Analysis Methods - Marsya Laila Ahyaliya; Rr. Rochmoeljati (Newinera Publisher, 2025)
Optimal service is essential to ensure citizen satisfaction in managing population administration. This study analyzes waste in the Electronic ID Card (KTP Elektronik) service process using the Lean Service and Root Cause Analysis (RCA) methods. The research was conducted at Office X through direct observation, interviews, and the distribution of questionnaires to eight respondents directly involved in the service process. The collected data included service process flows, activity durations, waste identification, and their root causes. Using the Value Stream Mapping (VSM) method and VALSAT tools, it was found that the total lead time was 1,953 seconds, but only 238 seconds (13%) were categorized as value-added activities. The dominant types of waste identified included waiting, duplication, defects, and unnecessary movement. Based on the score calculation results, Process Activity Mapping (PAM) was selected as the main VALSAT tool. RCA analysis using fishbone diagrams and the 5 Whys method revealed root causes such as inaccurate queue time estimates, repeated data entry, lack of supporting facilities, and inefficient workplace layout. The improvement recommendations include optimizing the online queuing system and adding supporting equipment such as tripods and printers. After improvements were implemented, the service time was reduced to 898 seconds, and the proportion of value-added activities increased to 27%, indicating that the application of Lean Service and RCA was effective in improving service efficiency.